2009
DOI: 10.1155/2009/823874
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of a Supersonic Flow Field around Solid Fuel on an Inclined Flat Plate

Abstract: This research adopts a shock tube 16 meters long and with a 9 cm bore to create a supersonic, high-temperature, and high-pressure flowfield to observe the gasification and ignition of HTPB solid fuel under different environments. Also, full-scale 3D numerical simulation is executed to enhance the comprehension of this complex phenomenon. The CFD (Computational Fluid Dynamics) code is based on the control volume method and the pre-conditioning method for solving the Navier-Stokes equations to simulate the compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For the numerical simulation of supersonic, high-temperature, and high-pressure flow fields in a long cylindrical shock tube [21], this study uses a multi-block grid approach, using CFD (computational fluid dynamics) code based on the control volume method and the preconditioning method for solving Navier-Stokes equations to model compressible and incompressible coupling problems. We define the inviscid flux vector 𝐹 ⃗ in the standard conservation form as follows:…”
Section: Numerical Simulation Of the Shock Wave Monitoringmentioning
confidence: 99%
“…For the numerical simulation of supersonic, high-temperature, and high-pressure flow fields in a long cylindrical shock tube [21], this study uses a multi-block grid approach, using CFD (computational fluid dynamics) code based on the control volume method and the preconditioning method for solving Navier-Stokes equations to model compressible and incompressible coupling problems. We define the inviscid flux vector 𝐹 ⃗ in the standard conservation form as follows:…”
Section: Numerical Simulation Of the Shock Wave Monitoringmentioning
confidence: 99%
“…In 2009, D.Simone 12 conducted the investigation of LiH as solid fuel and proved that LiH is a good candidate for SFSCRJ applicat ions, functioning as a high energy density bi-fuel system but also as a safe and compact hydrogen carrier. Hsu 13 ,14 used the Van Leer kappa-scheme to obtain the highresolution upwind differencing and carried the investigation on temperature field under the influence of shocks around the leading and trailing edge of plate-like HTPB solid fuel. Hsu's results showed that when the Mach number around the HTPB slab section was beyond 1.25, the flow field temperature was high enough for HTPB gasification and ignition.…”
Section: Introductionmentioning
confidence: 99%